The Impact of ERP Utilization in the Educational System on Enhancing Educational Quality Considering the Mediating Role of Technology Acceptance - Khazaei, Mohammad; Afrasiabi, Roya; Soleimanpour Omran, Mahboubeh (International Journal of Education and Cognitive Sciences, 2025)
Purpose: The primary objective of this study is to examine the impact of ERP utilization in the educational system on enhancing educational quality, considering the mediating role of technology acceptance. Methods and Materials: The statistical population of this study includes university professors and university staff at the expert level and above. Since the population was indeterminate, a sample of 384 individuals was determined based on Krejcie and Morgan’s table. The questionnaire was designed electronically, and its link was sent to the members of the statistical population. A researcher-made questionnaire was used in this study. Therefore, to determine its validity, the Content Validity Index (CVI) was employed. The results indicated that all 16 questionnaire items were approved by experts. Additionally, the reliability of the questionnaire was calculated using Cronbach’s alpha and was confirmed. The values were as follows: educational system (0.910), technology acceptance (0.891), and educational quality enhancement (0.793). Descriptive statistics were analyzed using SPSS 24, and structural equation modeling (SEM) was conducted using Smart-PLS 3. Findings: The results demonstrated that the hypothesis "ERP utilization in the educational system" has a significant impact on "educational quality enhancement." Additionally, "ERP utilization in the educational system" influences "technology acceptance." Moreover, "technology acceptance" affects "educational quality enhancement." Finally, "ERP utilization in the educational system" indirectly impacts "educational quality enhancement" through "technology acceptance." Conclusion: Based on the findings, it can be concluded that ERP utilization in the educational system significantly enhances educational quality, considering the mediating role of technology acceptance.